Clinical profile of patients with allergic contact dermatitis attending tertiary care hospital - Kalyanrao Y., Guruprasad; Nagure, Ashok Kumar B. (International Journal of Research in Dermatology, 2017)
Background: Contact dermatitis is an inflammatory response of the skin to various antigens and irritants. It accounts for a formidable proportion of dermatological consultations. It accounts for a formidable proportion of dermatological consultations. It is associated with significant morbidity, and it is one of the most common reasons for workmen’s compensation claims for skin diseases. Methods: The Methodology included detailed history especially of potential sensitisers in the environment, occupation, hobbies, any contact with external application of cosmetics, drugs, ointments. Emphases on past history were recorded regarding the mode of presentation, progression, medication taken and their effect on allergic contact dermatitis. Results: Allergic contact dermatitis due to Parthenium hysterophorus accounts for 80 (64%) cases, allergic contact dermatitis due to wearing apparel and jewellery accounts for 21 (16.8%) cases, due to topical medicaments 10 (8%), allergic contact dermatitis due to cosmetics and occupational (professional) antigen constituting 7 (5.6%) each. Conclusions: The most common and important mode of contact is from the pollen or dried leaf fragments flying in the air which settles on the skin, clothes and induces allergy which is known as Air borne contact dermatitis, this is more common in men, outdoor professions or those who spent more time in outdoor including froresters, labourers, engineers, sports person, hunters, gardeners and farmers.